Deforestation, Media, And Governance: A Discourse Network Approach to Indonesian Online News - Citra Safira; Yofiendi Indah Indainanto; Faizal Hamzah Lubis (Lektur: Jurnal Ilmu Komunikasi, 2025)
The study maps the discourse architecture of deforestation in Indonesian online media and assesses how actors, concepts, and issue frames are interconnected. Using a sample of 40 articles from eight portals (2024–2025), discourse-network analysis is employed to map the co-occurrence of actors and concepts. It interprets their position by connectivity and network density. The findings indicate two predominant competing blocks—environment versus economy-development—though they ultimately converge at the governance node (e.g., forest management policy, production forests, and palm oil plantation security). The Forest Management Policy operates as the axis, while Food and Energy serves as the corridor where consistent productivity claims are woven with ecological claims (coupled framing). At the level of actors, the government promotes the discourse, NGOs highlight ecological concerns, and academics act as brokers, providing evidential references to connect both blocs. These results validate the logic of agenda-setting: actors who are most prominently mentioned and cross-cut issues wield more influence in shaping the trajectory of public discourse. Policy implications are discussed, including enhancing data openness, providing space for diverse voices in the media, and defining better roles for knowledge users as connectors between arguments about production efficiency, food/energy security, and ecological boundaries.